Niche separation of pollen beetle parasitoids - Berger, Josef; Jönsson, Martin; Hedlund, Katarina; Anderson, Peter (Frontiers in Ecology and Evolution, 2015)
Species with similar resource requirements are commonly assumed to competitively exclude each other, unless they differentiate their ecological niches. Hence, parasitoid wasps that use the same host species need to find some way to avoid competition. The aim of this study was to identify the role of volatile cues from oilseed rape plants and the larval host in niche separation between three coexisting parasitoid species. We examined how Phradis interstitialis, Phradis morionellus and Tersilochus heterocerus, sympatric parasitoids of Brassicogethes aeneus, differ in their abundances, distribution on buds and flowers, and oviposition behavior in the field. Furthermore, we tested their preferences for odours from uninfested and infested oilseed rape plants in the bud and flowering stage, and their preferences for odours from three developmental stages of pollen beetle larvae in a two-choice olfactometer bioassay. P. interstitialis was active in the field early in the season, preferred odours of infested buds versus uninfested, and oviposited into buds which contained only pollen beetle eggs, while P. morionellus was active late in the season, preferred odours of infested buds as well as odours of infested flowers over uninfested, and oviposited into buds which contained only larvae. T. heterocerus was active throughout the season, and preferred odours of infested flowers over uninfested. Neither Phradis species were attracted to larval odours, whereas T. heterocerus was attracted to odours from first-instar pollen beetle larvae both in the absence of plant odours, and when presented simultaneously with uninfested plant odour. This suggests that the two Phradis species are separated on a temporal scale and that they parasitize different host stages, while the larval parasitoids P. morionellus and T. heterocerus are separated by choice of microhabitat. The former oviposits into larvae in buds, and the latter in flowers.